FORGETTER2 protein phosphatase and phospholipase D modulate heat stress memory in Arabidopsis. (7th August 2020) - Urrea Castellanos, Reynel; Friedrich, Thomas; Petrovic, Nevena; Altmann, Simone; Brzezinka, Krzysztof; Gorka, Michal; Graf, Alexander; Bäurle, Isabel
SUMMARY: Plants can mitigate environmental stress conditions through acclimation. In the case of fluctuating stress conditions such as high temperatures, maintaining a stress memory enables a more efficient response upon recurring stress. In a genetic screen for Arabidopsis thaliana mutants impaired in the memory of heat stress (HS) we have isolated the FORGETTER2 ( FGT2 ) gene, which encodes a type 2C protein phosphatase (PP2C) of the D‐clade. Fgt2 mutants acquire thermotolerance normally; however, they are defective in the memory of HS. FGT2 interacts with phospholipase D α2 (PLDα2), which is involved in the metabolism of membrane phospholipids and is also required for HS memory. In summary, we have uncovered a previously unknown component of HS memory and identified the FGT2 protein phosphatase and PLDα2 as crucial players, suggesting that phosphatidic acid‐dependent signaling or membrane composition dynamics underlie HS memory. Significance Statement: Plants are primed by a previous exposure to high temperatures, and this enables them to be better prepared for future stress incidents. While previous studies point to the importance of chromatin regulation in this heat stress‐induced memory, this work identifies a crucial role for protein dephosphorylation and lipid dynamics at the plasma membrane–cytosol interface.